Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja Terhadap Disiplin Kerja Guru di SMP Negeri Se Kecamatan Prabumulih Timur - Nurmawan Srimawati; Tri Widayatsih; Mahasir (CV. ULIL ALBAB CORP, 2025)
This study aims to determine the effect of principal leadership and work motivation on teacher work discipline. This research was conducted in State Junior High Schools in East Pabumulih District. This type of research is quantitative research. The sample used in this study was 144 teachers consisting of 4 State Junior High Schools in East Pabumulih District. The data collection technique used a questionnaire. The data analysis technique used quantitative descriptive analysis techniques, simple regression tests and multiple regression tests. The results of this study state that 1) there is a significant influence of principal leadership on teacher work discipline in State Junior High Schools in East Pabumulih District; 2) there is a significant influence of work motivation on teacher work discipline in Public Junior High Schools throughout Pabumulih Timur District 3) there is a significant influence of principal leadership and work motivation on teacher work discipline in Public Junior High Schools throughout Pabumulih Timur District